The impact of auditor reputation impairments on private-client market share - Acito, Andrew A.; Pittman, Jeffrey A.; Truelson, J. Mike (Review of Accounting Studies, 2026)
Abstract We examine the impact of auditors’ reputation impairments on their private-client market share to explore how conducting low-quality audits affects auditors’ broader client portfolios. Prior evidence implies that an audit office loses public-client market share after a client announces a restatement. However, auditors’ private clients may be less concerned about auditor reputation and quality, given that they have lower agency costs and their financial statement users are often creditors that can rely on direct monitoring to narrow information asymmetry. Also, differences between public and private company audits cast doubt on whether public-client restatements are relevant to private clients. We find that the private-client market share of a Big Four audit office falls by, on average, 5 percent the year after a public client announces a restatement. This evidence suggests that Big Four offices cannot simply replace lost public-client revenue with private-client revenue after suffering reputation damage.